Heavy metal contamination and eutrophication effects on bacterial communities in the Han River basin - Fei Xiong; Cejia Yao; Dongdong Zhai; Hongyan Liu; Wang Dong; Yuanyuan Chen (Ecological Indicators)
The Han River, a key water source for China’s South-to-North Water Diversion Project, faces ecological challenges due to urbanization-driven heavy metal pollution and eutrophication. This study analyzed microbial communities in sediment samples from 15 sites using 16S rDNA sequencing. Our findings revealed a significant decrease in α-diversity with increasing copper (Cu) concentration, with the downstream region (group L) exhibiting higher diversity compared to the upstream region (group U). Group U was dominated by Alphaproteobacteria, while Clostridia prevailed in groups M and L. Analysis of β-nearest taxon index (βNTI) indicated that stochastic processes primarily shaped community assembly. Redundancy analysis (RDA) identified Cu, Fe, and Cr as key environmental factors influencing bacterial community composition in group U, while COD, Chl_a, pH, TN, and TP affected groups M and L. The study emphasizes the importance of addressing heavy metal pollution in eutrophic waters to protect microbial community diversity.